Stanovení frekvence C282Y mutace pro populaci Ceské republiky a Hemochromatosis. Stanovení frekvence C282Y mutace pro populaci Ceské republiky a citlivá detekce hemochromatózy z Guthrie karet - Zdárský, E; Horák, J; Stríteský, J; Heirler, F (Casopis lekaru ceskych, 1999)
BACKGROUND: Hereditary haemochromatosis (HH) is a multi-organ disease characterized by increased deposition of iron in some tissues. When discovered early the disease is curable. The Caucasian population is burdened with a high incidence of carriers and homozygotes. The recent discovery of the gene for haemochromatosis (HFE) and of the major mutation C282Y makes direct diagnosis possible. METHODS AND RESULTS: Exploiting a newly-designed polymerase chain reaction system, we determined the frequency of the C282Y mutation of the HFE gene in the Czech population by analysis of 278 chromosomes from anonymous clients of an in vitro fertilization centre (128 male and 150 female karyotypes respectively). There were 14 heterozygotes of the C282Y mutation (6 males and 8 females) and no asymptomatic homozygotes. All 12 patients with classically diagnosed haemochromatosis were homozygous for the C282Y mutation. Twelve Guthrie cards ten years old were tested as a source of the PCR signal for C282Y with a positive result in all cases (100% efficiency). CONCLUSIONS: Our data suggest that the approximate frequency of heterozygotes (carriers) of hereditary haemochromatosis in the Czech population is 1:10 which is comparable with data from the Central European region. The frequency of the major mutation among patients with HH was 100% (12/12), however, the difference with data from neighbouring countries (Austria, Germany) cannot be considered significant due to the small number of patients tested. We also showed the possibility of a retro-diagnosis of the presence/absence of C282Y mutation from Guthrie cards.
Keywords: hemochromatóza; chorobopisy; Medical Records; Genes, MHC Class I; Hemochromatosis; Česká republika; polymerázová řetězová reakce; Polymerase Chain Reaction; Sensitivity and Specificity; mužské pohlaví; geny MHC třídy I; novorozenecký screening; mutace; Czech Republic; Neonatal Screening; ženské pohlaví; Mutation; Humans; frekvence genu; senzitivita a specificita; Gene Frequency; Female; lidé; Male